Visual field loss patterns in dominant and recessive optic atrophy based on OPA1 archetypes - Cascavilla, Maria Lucia; Coutinho, Catarina; Battista, Marco; Zanchetta, Ferdinando; Galzignato, Alice; Lari, Giorgio; Albertini, Stefano; Brotto, Luigi; Nucci, Paolo; Fioresi, Rita; Bandello, Francesco; Barboni, Piero (Acta ophthalmologica (Oxford, England), 2024)
Aims/Purpose: Identification and quantification of visual field loss patterns of dominant optic atrophy forms (ACO2 and AFG3L2 mutations) and recessive optic atrophy form (WFS1 mutation, Wolfram Syndrome, WS) based on machine learning‐obtained archetypes for OPA1‐Dominant Optic Atrophy (DOA). Methods: Five patients affected by hereditary optic neuropathies carrying ACO2 gene mutations, 5 with AFG3L2 mutations, and 20 with WFS1 mutations were enrolled. Visual field (VF) tests performed by SITA standard 30–2 or 24–2 Humphrey VF analyzer (Carl Zeiss Meditec, Dublin, CA, USA) were collected for these patients. The VFs of these rare mutations (30% WFS1, 10% ACO2 and 3% AFG3L2 [1]) were decomposed and quantified according to the archetypes (AT) obtained in the unsupervised machine learning model developed for the OPA1 mutation. Results: The archetype analysis (AA)‐model developed for the DOA‐OPA1 mutation is composed of twelve ATs, with the central, the ceco‐central, and the para‐central as the most significant ones. For WS patients, the VF‐decomposition was mostly made up of ATs resembling more severe abnormalities, while for the ACO2 and AFG3L2‐affected patients the most important ATs were similar to the OPA1 cases. Conclusions: The developed AA‐model based on OPA1‐DOA affected patients enabled the decomposition of VFs of more rare optic atrophy mutations. The association of weights to the different ATs for patient‐specific VFs showed to be a possible option to identify and quantify the most important patterns of visual field loss in such particular cases of autosomal dominant or recessive optic neuropathies. A pattern‐specific visual field loss might strengthen the differential diagnosis between OPA1 and other mutations and support future clinical and therapeutic trials. References 1. Rocatcher A, Desquiret‐Dumas V, Charif M, et al. The top 10 most frequently involved genes in hereditary optic neuropathies in 2186 probands. Brain 2023; 146(2): 455–460. doi: 10.1093/brain/awac395